Ion Selectivity in the Selectivity Filters of Acid-Sensing Ion Channels - Dudev, Todor (Sci Rep, 2015)
Sodium-selective acid sensing ion channels (ASICs), which belong to the epithelial sodium channel (ENaC) superfamily, are key players in many physiological processes (e.g. nociception, mechanosensation, cognition, and memory) and are potential therapeutic targets. Central to the ASIC's function is its ability to discriminate Na(+) among cations, which is largely determined by its selectivity filter, the narrowest part of an open pore. However, it is unclear how the ASIC discriminates Na(+) from rival cations such as K(+) and Ca(2+) and why its Na(+)/K(+) selectivity is an order of magnitude lower than that of the ENaC. Here, we show that a well-tuned balance between electrostatic and solvation effects controls ion selectivity in the ASIC1a SF. The large, water-filled ASIC1a pore is selective for Na(+) over K(+) because its backbone ligands form more hydrogen-bond contacts and stronger electrostatic interactions with hydrated Na(+) compared to hydrated K(+). It is selective for Na(+) over divalent Ca(2+) due to its relatively high-dielectric environment, which favors solvated rather than filter-bound Ca(2+). However, higher Na(+)-selectivity could be achieved in a narrow, rigid pore lined by three weak metal-ligating groups, as in the case of ENaC, which provides optimal fit and interactions for Na(+) but not for non-native ions.